Determination of the Optimum Cost Function for an Electric Arc Furnace and Ladle Furnace System by Using Energy Balance - (:unkn) unknown (TAYLOR & FRANCIS INC, 2012)
Metallurgical thermodynamics belongs to the field of chemical thermodynamics. It is of major importance to define an energy efficient strategy for the optimization of steelmaking plants. In this study, cost function for materials and energy usage in an electric arc furnace and ladle furnace at a steelmaking facility in Turkey is determined. Then, the cost function is solved by using the linear optimization method and versus constraints functions which are formed according to steel productions in the firm. After running a program used for optimization, some results are obtained. Production wastes and heavy melting scraps change from 910 to 5,500 kg and from 0 to 27,475.5 kg, respectively. Pig varies from 4,983 to 33,425 kg. Its minimum value is Ck22 1.1151 steel type and maximum value 38Cr2 1.7003 steel type. Coke value changes from 900 to 1,000 kg. Oxygen is varying as 4,000 or 4,180 kg for different steel types.
Keywords: electric arc furnace (EAF); energy optimization; ladle furnace (LF); liquid steel; steel making; Turkey; OPTIMIZATION; STEELMAKING